Da fé à festa : uma análise ritual, simbólica e performática dos festejos da lavagem do Rosário Largo em Penedo, Alagoas - Silva Júnior, Cláudio Gomes da (2013)
Such research aims to study the Feast Laundering dedicated to orisha Oxalá held at wide of Rosário, Penedo, Alagoas. The ritual takes place for about thirteen years, and was inspired by the traditional washing of Lord of Bonfim in Salvador, through the redefinition symbolic elements. During its realization are washed the churchyard of the Church of Our Lady of the Rosary of Black and Alley of Laziness, spaces that represent the opposition between the sacred and the profane, which are taken by the festivities of the street carnival after washing. The ritual presents itself as a festival of purification, being the greatest expressions of religious syncretism in the city, and develops through an action that relates Catholicism and Candomblé honoring Oxalá, the orisha of creation, but also have a reference to African mythology. The goal is to develop a discussion about the meaning of the ritual washing of the Rosary from the ethnographic work, analyze the involvement of the participants and their performances, ritual symbols, its organizational and historical context, as a ritual that combines faith and celebration and that develops over time and space festive carnival.